2010
DOI: 10.1007/s00520-010-0888-8
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effects of low-level laser therapy in the management of breast-cancer-related lymphedema

Abstract: Patients with BCRL received additional benefits from LLLT when used in conjunction with standard lymphedema treatment. These benefits include reduction in limb circumference, pain, increase in range of motion and scar mobility. Additionally, two cycles of LLLT were found to be superior to one in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 17 publications
0
55
1
Order By: Relevance
“…Six of the nine studies reported on adverse events or discussed harm [6,[21][22][23][24]27]. Dirican et al [23] reported development of cellulitis in one participant in the LLLT group.…”
Section: Harmmentioning
confidence: 98%
See 1 more Smart Citation
“…Six of the nine studies reported on adverse events or discussed harm [6,[21][22][23][24]27]. Dirican et al [23] reported development of cellulitis in one participant in the LLLT group.…”
Section: Harmmentioning
confidence: 98%
“…This single-group pre-test/post-test study [23] investigated the effect of LLLT on 17 women with BCRL. All patients used compression garments or bandaging, and two used a pneumatic pump during the course of the study intervention.…”
Section: Dirican Et Al 2011mentioning
confidence: 99%
“…The proposed underlying mechanism is that LLLT increases the lymphatic drainage by stimulating the formation of new lymph vessels, by improving the lymphatic motricity, and by preventing the formation of fibrotic tissue [33][34][35][36].…”
Section: Lllt For the Management Of Bcrlmentioning
confidence: 99%
“…It is backed by longstanding clinical experience. Other modalities such as low-level laser therapy (LLLT) and surgical approaches have demonstrated beneficial effects for selected patients with lymphedema, and could be considered as an adjunct therapy alongside standard treatment methods [8,9]. Intermittent pneumatic compression pump (IPC) devices are pneumatic cuffs connected to pumps that mimic the naturally occurring pump effect of muscles contracting around peripheral lymphatics [10].…”
Section: Introductionmentioning
confidence: 99%